Znaleziska wczesnośredniowiecznych akcesoriów kupieckich z Santoka na tle porównawczym - Zamelska-Monczak, Kinga (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2020)
This article presents a collection of early medieval trade accessories, folded scales and weights excavated by archaeologists on site no. 1 in Santok (Lubusz province). The collection of weights is formally and chronologically diverse. The oldest specimens come from structures dated back to the 4th quarter of the 9th century, the youngest to the 14th century. Metallographic analyses indicate that to produce the scales and weights, alloys of copper, different types of bronze and brass were used. The fact that exchange of goods in Santok took place earlier than in the other regions of Wielkopolska is evidence of close contacts with the then economic Baltic zone.